Can Macroeconomic Variables Explain Long Term Stock Market Movements? A Study of Nepali Capital Market - Phuyal, Niranjan (Journal of Business and Management Research, 2016)
The quest of whether there is a long-run relation between macroeconomic variables and stock prices has found significant place in literature of finance. An existence of such relation would assure long-term investors a confidence in the market as long as the macroeconomic environment is sound. This study investigated using Johansen’s cointegration method, whether a long-term association of selected macroeconomic variables existed with stock prices in the emerging market like Nepali stock market. For this objective, monthly data from January 2003 to December 2012 were used with a set of six macroeconomic variables and stock market return. The results indicated that the Nepali stock market had a long run equilibrium relationship with a set of macroeconomic variables, like inflation rate, interest rate and remittance flow with the short term disequilibrium corrected by 1.79% on monthly basis. It further showed that there was Granger causality between them. In the short run, the stock market index was affected by the lag values of NEPSE index up to six levels and remittance income, as shown by Wald test. These findings hold practical implications for policy makers, stock market regulators, investors and stock market analysts. Journal of Business and Management Studies Vol.1(1) 2016: 26-38